2018
DOI: 10.1037/cbs0000107
|View full text |Cite
|
Sign up to set email alerts
|

Agression indirecte à l’âge scolaire primaire et comportements de prise de risque durant le secondaire chez les filles.

Abstract: Les comportements d’agression peuvent entraîner de graves difficultés d’adaptation, dont un risque accru de s’engager dans des comportements de prise de risque à l’adolescence. Dans un échantillon composé exclusivement de filles, la présente étude vise à examiner si l’agression indirecte évaluée par les pairs à la fin de l’école primaire peut prédire le développement de divers comportements de prise de risque autorapportés au secondaire (comportements délinquants, consommation de psychotropes et activité sexue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Most children manifest low-to-moderate decreasing levels of IA, but a group of them manifest high or increasing levels of IA (Boutin et al, 2017, 2021; Chen et al, 2019; Pagani et al, 2010; Vaillancourt et al, 2007), and this high use can persist into adulthood (Coyne et al, 2020; Vaillancourt & Farrell, 2021). Even if the latter are in minority, in addition to causing considerable harm to others (Casper & Card, 2017), these high users of IA are at elevated risk for future detrimental outcomes, such as anxiety, depression, delinquency, drug use, and risky sexual behaviors (Boutin et al, 2018; Card et al, 2008; Chen et al, 2019; Cleverley et al, 2012; Ehrenreich et al, 2016). These risks were found even after controlling for direct forms of aggression, like physical aggression.…”
Section: Psychopathic Traits Dimensions and Iamentioning
confidence: 99%
See 2 more Smart Citations
“…Most children manifest low-to-moderate decreasing levels of IA, but a group of them manifest high or increasing levels of IA (Boutin et al, 2017, 2021; Chen et al, 2019; Pagani et al, 2010; Vaillancourt et al, 2007), and this high use can persist into adulthood (Coyne et al, 2020; Vaillancourt & Farrell, 2021). Even if the latter are in minority, in addition to causing considerable harm to others (Casper & Card, 2017), these high users of IA are at elevated risk for future detrimental outcomes, such as anxiety, depression, delinquency, drug use, and risky sexual behaviors (Boutin et al, 2018; Card et al, 2008; Chen et al, 2019; Cleverley et al, 2012; Ehrenreich et al, 2016). These risks were found even after controlling for direct forms of aggression, like physical aggression.…”
Section: Psychopathic Traits Dimensions and Iamentioning
confidence: 99%
“…While the conceptual similarity between psychopathic traits and IA mostly concerns the narcissism–grandiosity dimension, empirical associations have also been reported between IA and other dimensions of psychopathic traits that appear conceptually distinct from IA. Notably, in samples of children aged 8–15, IA (Ando et al, 2005; Boutin et al, 2018) and relational aggression (Crapanzano et al, 2010; Kamper & Ostrov, 2013; Spieker et al, 2012) have been associated to behavioral impulsivity, risk-taking, and sensation-seeking, which are core features of the impulsivity–irresponsibility dimension of psychopathic traits. In a longitudinal study, Espelage et al (2018) showed that self-reported behavioral impulsivity in participants aged 10–14 was positively associated with relational aggression both at the within-person and between-persons level over 2 years.…”
Section: Psychopathic Traits Dimensions and Iamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if a child does not present CP in addition to their high IA use, there is a great possibility that they will not be offered mental health services (Marsee et al, 2014). Therefore, considering that IA is linked (over and above other behavioral problems) to detrimental outcomes, such as anxiety, depression, delinquency, drug use and risky sexual behaviors (Boutin et al, 2018;Card et al, 2008;Cleverley et al, 2012), it will be crucial for school behavior specialists to start considering not only children's more noticeable behavioral difficulties but also their problematic social interactions involving IA.…”
Section: Limits Strengths and Conclusionmentioning
confidence: 99%